Anti-stripping printed fabric and processing method thereof

By pretreating the grey fabric with a dipping solution of rare earth-chitosan complex and baking soda in printed fabrics, and combining the printing paste of oak bark extract and other ingredients treated with plant mucus, the problem of difficult to take into account the anti-peeling ability and softness of printed fabrics is solved, and better anti-peeling performance and anti-bacterial effect are achieved.

CN119571647APending Publication Date: 2025-03-07GAOFAN (ZHEJIANG) INFORMATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411751453.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the event of friction or washing, existing printed fabrics do not adhere firmly to the printing pattern and the substrate, resulting in the printing being easily shedded or faded. High-quality dyes and additives pose environmental and human health risks, and increasing additives will affect the softness of the fabric.

Method used

The impregnation liquid is prepared by using rare earth-chitosan complex and baking soda. The grey cloth is pretreated through the impregnation liquid to form a protective film to enhance the bonding force between the printing paste and the grey cloth fiber. At the same time, the printing color paste is prepared using ingredients such as oak bark extract treated with plant mucus to enhance the depth and uniformity of the printing.

Benefits of technology

It improves the anti-peeling ability and softness of printed fabrics, extends the service life and aesthetics of the fabrics, and provides antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165098730000071
    Figure BDA0005165098730000071
  • Figure BDA0005165098730000081
    Figure BDA0005165098730000081
  • Figure BDA0005165098730000091
    Figure BDA0005165098730000091
Patent Text Reader

Abstract

The invention relates to an anti-stripping printed fabric and a processing method thereof, and relates to the technical field of garment fabric preparation, and the printed fabric is prepared from the following raw materials in parts by weight: a gray fabric, steeping liquor for pretreating the gray fabric and printing paste for printing the gray fabric, comprising 5-7 parts of a rare earth-chitosan complex, 0.5-1 part of baking soda and 50-60 parts of ethanol. The rare earth-chitosan complex is obtained by treating rare earth and chitosan with tartaric acid; the printing paste is prepared from the following raw materials in parts by weight: 10-15 parts of oak bark powder, 2-4 parts of a seaweed extract, 2-4 parts of a coral extract, 1-3 parts of xanthan gum, 1-3 parts of elaeagnus angustifolia gum, 5-7 parts of pigment and 100-120 parts of deionized water. The oak bark powder is obtained by treating an oak bark extract with plant mucus. During preparation, the gray fabric is subjected to impregnation liquid pretreatment, and the impregnation liquid is prepared from a rare earth-chitosan complex and baking soda, so that the binding force between subsequent gray fabric fibers and printing paste is enhanced, and the anti-stripping capacity of the fabric is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of clothing fabric preparation, in particular to an anti-stripping printed fabric and a processing method thereof. Background Art

[0002] Printed fabric refers to fabric with patterns or colors added to the surface of the fabric through printing technology. This kind of fabric is widely used in many fields such as clothing, home decoration, handbags, etc. Printing can be done in many ways, such as screen printing, digital printing and thermal transfer. The anti-stripping ability of printed fabric refers to the degree of adhesion between the printed pattern and the substrate under friction or washing. The purpose of enhancing the anti-stripping ability is to ensure that the printed pattern can remain stable during use and is not easy to fall off or fade, thereby extending the service life and aesthetics of the fabric.

[0003] In order to enhance the anti-stripping ability of printed fabrics, high-quality dyes and auxiliaries are generally selected. However, existing dyes and auxiliaries usually contain chemical synthetic materials, which pose potential risks to the environment and human health. At the same time, the penetration ability of dyes and auxiliaries is poor, which will lead to uneven color and insufficient adhesion, affecting the printing quality and the overall performance of the fabric. In order to enhance the anti-stripping ability of printed fabrics, a large amount of auxiliaries is generally required to be added, which leads to a greater impact on the softness of the fabric and significantly increases the hardness of the fabric.

[0004] To this end, we provide a peeling-resistant printed fabric and a processing method thereof to solve the above-mentioned problems. Summary of the invention

[0005] The purpose of the present invention is to provide an anti-stripping printed fabric and a processing method thereof in view of the problems of the background technology.

[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:

[0007] A peeling-resistant printed fabric, the raw materials for preparing the fabric include grey cloth, an impregnation solution for pretreating the grey cloth, and a printing paste for printing the grey cloth, wherein the raw materials for preparing the impregnation solution include, by weight, 5-7 parts of a rare earth-chitosan complex, 0.5-1 parts of baking soda, and 50-60 parts of ethanol; the rare earth-chitosan complex is obtained by treating rare earth and chitosan with tartaric acid; the raw materials for preparing the printing paste include, by weight, 10-15 parts of oak bark powder, 2-4 parts of seaweed extract, 2-4 parts of coral extract, 1-3 parts of xanthan gum, 1-3 parts of angustifolia gum, 5-7 parts of colorant, and 100-120 parts of deionized water; the oak bark powder is obtained by treating an oak bark extract with plant mucus.

[0008] As a further optimization scheme of the present invention, the mass ratio of the rare earth, chitosan and tartaric acid is 1:3-3.5:0.7-0.8.

[0009] As a further optimization scheme of the present invention, the rare earth is a mixture of lanthanum oxide powder and cerium oxide powder with a particle size range of 10-50 nm, and the mass ratio of the lanthanum oxide powder to the cerium oxide powder is 1:1-1.2.

[0010] As a further optimization scheme of the present invention, the preparation steps of the rare earth-chitosan complex are: dispersing chitosan in 5-7 times the mass of deionized water to obtain a chitosan solution, dispersing rare earth in 5-7 times the mass of deionized water to form a rare earth solution, slowly adding the rare earth solution to the chitosan solution under stirring, slowly adding tartaric acid after mixing evenly, applying ultrasound with a frequency of 15-20KHz and a time of 25-35min to the dispersion after mixing evenly, then controlling the temperature of the dispersion to 50-55°C, the pH to 5-6, the reaction time to 2-3h, and after the reaction is completed, cooling the mixture, standing it to allow the complex to precipitate, and drying the precipitate to obtain the rare earth-chitosan complex.

[0011] As a further optimization scheme of the present invention, the preparation steps of the impregnation solution are: dispersing the rare earth-chitosan complex in ethanol, mixing evenly to obtain a rare earth-chitosan complex solution, then dispersing baking soda in the remaining ethanol, mixing evenly to obtain a baking soda solution, and then slowly mixing the rare earth-chitosan complex solution and the baking soda solution, and gently stirring until they are uniform.

[0012] As a further optimization scheme of the present invention, the mass ratio of the oak bark extract to the plant mucus is 1:0.3-0.5; the plant mucus is a mixture of one or more of aloe mucus, cactus mucus and okra mucus.

[0013] As a further optimization scheme of the present invention, the preparation steps of the oak bark powder are: dispersing the oak bark extract in 8-10 times the mass of deionized water, adding plant mucus after mixing evenly, applying ultrasound with a frequency of 20-25KHz and a time of 10-15min to the dispersion after mixing evenly, and then controlling the temperature of the dispersion to 40-50°C, the pH to 4-5, and standing for 1-2h. After the reaction is completed, drying is carried out in a low-temperature dryer until a solid is formed, and the oak bark powder is obtained after crushing.

[0014] As a further optimization scheme of the present invention, the preparation steps of the printing paste are: dissolving xanthan gum and angustifolia gum in deionized water and letting it stand for 15-20 minutes to obtain a colloid mixture, dispersing oak bark powder, seaweed extract and coral extract in deionized water in another container in turn, adding the colloid mixture thereto after mixing evenly, adding colorant and deionized water based on the required color depth and viscosity after mixing evenly, applying ultrasound with a frequency of 20-25KHz and a time of 15-20 minutes after mixing evenly to obtain a printing paste.

[0015] As a further optimization solution of the present invention, the grey cloth is woven from polyester fibers.

[0016] The present invention also provides a method for processing an anti-stripping printed fabric, comprising the following steps:

[0017] S1. Spray the impregnation liquid onto the surface of the grey cloth according to the printing template and leave it in a ventilated environment for 20-30 minutes;

[0018] S2, controlling the temperature of the printing paste to 50-55°C, and printing the pattern according to the printing template;

[0019] S3. After printing is completed, the grey cloth is dried and cured to obtain a peel-resistant printed fabric.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention pre-treats the grey cloth with an impregnation liquid and then performs printing, so that a protective film can be formed on the surface of the grey cloth fiber by the impregnation liquid, thereby enhancing the bonding force between the grey cloth fiber and the printing paste, thereby improving the anti-stripping ability of the fabric.

[0022] 2. The present invention uses rare earth-chitosan complex and baking soda to prepare the impregnation solution. The complex formed by chitosan and rare earth can interact with the printing paste, enhance the binding force between the printing paste and the grey cloth fiber, prevent the printing paste molecules from falling off, and provide certain antibacterial properties.

[0023] 3. The present invention adopts oak bark extract treated with plant mucus to prepare printing paste, and cooperates with seaweed extract, coral extract, xanthan gum, angustifolia gum and other ingredients to form a stronger binding force with the surface of grey cloth fiber during the printing process, and can penetrate into the interior of the grey cloth fiber, thereby further improving the anti-stripping ability of the printed fabric. DETAILED DESCRIPTION

[0024] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.

[0025] 1. Main instruments and materials

[0026] The instruments used in the present invention, such as ultrasonic equipment, mechanical stirring equipment, and dryer, are conventional instruments known to those skilled in the art unless otherwise specified, and the reagents and other materials used, unless otherwise specified, are commercially available products.

[0027] The oak bark extract is prepared by crushing the dried oak bark and soaking it in 70% ethanol at 30-40°C for 24 hours. The crushing particle size is 80-120 meshes, and the solid-liquid ratio is 1:10 (g / mL). The extract is then filtered to remove impurities and insoluble matter. The filtrate is then concentrated by a concentration device (such as a concentration tank) at a concentration temperature of 50-60°C to about 10% of the total volume. Finally, the extract is freeze-dried to obtain the extract.

[0028] The seaweed extract is prepared by crushing the dried seaweed and soaking it in 70% ethanol at 30-40°C for 24 hours, with a crushing particle size of 80-120 meshes and a solid-liquid ratio of 1:12 (g / mL). The extract is then filtered to remove impurities and insoluble matter, and the filtrate is then concentrated through a concentration device (such as a concentration tank) with the concentration temperature controlled at 50-60°C to about 10% of the total volume, and finally freeze-dried to obtain the extract.

[0029] The coral extract is obtained by crushing the dried seaweed and soaking it in 85% ethanol at 30-40°C for 48 hours. The crushing particle size is 80-120 meshes, and the solid-liquid ratio is 1:15 (g / mL). The extract is then filtered to remove impurities and insoluble matter. The filtrate is then concentrated through a concentration device (such as a concentration tank) with the concentration temperature controlled at 50-60°C to about 10% of the total volume. Finally, the extract is freeze-dried to obtain the extract.

[0030] 2. Implementation of the experiment

[0031] Select the raw materials for preparing the impregnation liquid and printing paste of different components, as shown in Table 1, and prepare the printed fabric according to the following processing method:

[0032] S1. Dispersing the rare earth-chitosan complex in ethanol, mixing evenly to obtain a rare earth-chitosan complex solution, dispersing baking soda in the remaining ethanol, mixing evenly to obtain a baking soda solution, and then slowly mixing the rare earth-chitosan complex solution with the baking soda solution, gently stirring until a uniform state is obtained to obtain an impregnation solution, spraying the impregnation solution on the surface of a grey cloth woven from polyester fibers according to a printing template, and standing in a ventilated environment for 25 minutes;

[0033] The rare earth-chitosan complex is obtained by treating rare earth and chitosan with tartaric acid in a mass ratio of 1:3.2:0.7, and the rare earth is a mixture of lanthanum oxide powder and cerium oxide powder with a particle size range of 10-50 nm in a mass ratio of 1:1. Specifically, chitosan is dispersed in 6 times the mass of deionized water to obtain a chitosan solution, and rare earth is dispersed in 6 times the mass of deionized water to form a rare earth solution. Under stirring, the rare earth solution is slowly added to the chitosan solution, and tartaric acid is slowly added after mixing evenly. After mixing evenly, ultrasonic waves with a frequency of 18KHz and a time of 30 minutes are applied to the dispersion, and then the temperature of the dispersion is controlled to 52°C, the pH is 5.5, and the reaction time is 2.5 hours. After the reaction is completed, the mixture is cooled, and the complex is allowed to stand to precipitate, and the precipitate is dried to obtain the rare earth-chitosan complex.

[0034] S2, dissolving xanthan gum and angustifolia gum in deionized water and standing for 18 minutes to obtain a colloid mixture, dispersing oak bark powder, seaweed extract and coral extract in deionized water in another container in turn, adding the colloid mixture thereto after mixing evenly, adding corresponding colorants and deionized water based on the required color depth and viscosity after mixing evenly, applying ultrasound at a frequency of 22KHz for 18 minutes after mixing evenly to obtain a printing paste, controlling the temperature of the printing paste to 52°C, and printing a pattern according to the printing template;

[0035] The oak bark powder is obtained by treating the oak bark extract with a mass ratio of 1:0.4 with plant mucus, and the plant mucus is okra mucus. Specifically, the oak bark extract is dispersed in 9 times the mass of deionized water, and the plant mucus is added thereto after being mixed evenly. After being mixed evenly, ultrasonic waves with a frequency of 22KHz and a time of 12min are applied to the dispersion, and then the temperature of the dispersion is controlled to 45°C, the pH is 4.5, and the standing time is 1.5h. After the reaction is completed, it is dried in a low-temperature dryer until a solid is formed, and the oak bark powder is obtained after being crushed;

[0036] S3. After printing is completed, the grey cloth is dried and cured to obtain a peel-resistant printed fabric.

[0037] Table 1 Raw material components for preparing impregnation liquid and printing paste

[0038]

[0039] Note: “-” means no addition, ordinary rare earth-chitosan complex refers to the complex that has not been treated with tartaric acid, and ordinary oak bark powder refers to the oak bark extract that has not been treated with plant mucus.

[0040] Take several groups of printed fabrics prepared with AI impregnation liquid and printing paste of the same mass, make uniform test samples with the specifications of 20cm×20cm×0.5mm, and conduct the following tests on the samples respectively:

[0041] (1) Friction test:

[0042] Fix the printed fabric on the friction head of the testing machine, rub the surface of the fabric at a specified speed and stroke under a certain pressure, and observe the wear degree of the printed fabric after a certain number of frictions. Rating the anti-stripping ability is divided into 5 levels, and the higher the level, the better the anti-stripping ability.

[0043] (2) Peel strength test:

[0044] Use a peel tester to perform a peel test on the printed edge according to standards (such as ASTMD903 or ISO 2411), fix the sample on the fixture, gradually apply tension, and record the maximum force value during peeling. The higher the maximum force value, the better the sample's anti-peeling ability.

[0045] (3) Softness test:

[0046] The sample is placed on a bending tester and the force required to apply a certain angle is measured to evaluate softness. The higher the bending force value, the worse the softness of the sample.

[0047] Table 2 Performance parameters of each test sample

[0048]

[0049]

[0050] Note: The friction level is expressed as 1-5, as shown in Table 3 below:

[0051] Table 3 Friction grade

[0052]

[0053] 3. Results Analysis

[0054] 1. Combined with the above table, the test data of A, B, C printed fabrics are compared with other printed fabrics. It can be seen that the friction level and peeling tension of the fabrics are significantly better than those of other printed fabrics, indicating that the anti-peeling ability of A, B, C printed fabrics is better, and the bending force of the fabrics is also better than that of other printed fabrics, indicating that the softness and comfort of A, B, C printed fabrics are not significantly reduced while ensuring the anti-peeling ability, which solves the problem that it is difficult to balance the anti-peeling ability and softness of traditional printed fabrics.

[0055] 2. Combined with the above table, the comparison of the test data of D printed fabric and A printed fabric shows that when preparing the impregnation solution, the addition of baking soda can effectively improve the anti-stripping ability and softness of the printed fabric. Baking soda is an alkaline substance, which can make the grey cloth fibers expand and open to a certain extent, increase the channels for the printing paste molecules to enter the interior of the grey cloth fibers, and the printing paste molecules can more easily penetrate into the interior of the grey cloth fibers, thereby improving the depth and uniformity of printing, and thus improving the anti-stripping ability of the fabric.

[0056] 3. Combined with the above table, the comparison of the test data of E, G printed fabrics and A printed fabrics shows that the pretreatment effect of the grey cloth is greatly reduced when the impregnation solution prepared by not adding rare earth-chitosan complex or adding ordinary rare earth-chitosan complex is prepared. The anti-stripping ability and softness of the printed fabric are significantly reduced. Chitosan is a natural polymer compound with good biocompatibility and adsorption properties. The complex formed with rare earth is used in the preparation of printed fabrics to improve the anti-stripping ability of the fabric. The groups in the chitosan molecules form coordination bonds with rare earth to form a protective film on the surface of the grey cloth fiber. The complex can interact with the printing paste to enhance the binding force between the printing paste and the grey cloth fiber and prevent the shedding of the printing paste molecules. In addition, chitosan itself has certain antibacterial properties. The use of rare earth-chitosan complexes can not only improve the firmness of the printing paste, but also make the printed fabric have a certain antibacterial effect. After tartaric acid treatment, the stability of the printing paste on the grey cloth fiber can be further enhanced.

[0057] 4. Combined with the above table, the comparison of the test data of F printed fabric and A printed fabric shows that without preparing the impregnation liquid and pre-treating the grey cloth with the impregnation liquid, the anti-stripping ability and softness of the printed fabric are significantly reduced. By pre-treating the grey cloth with the impregnation liquid and then printing, a protective film can be formed on the surface of the grey cloth fiber through the impregnation liquid, which enhances the bonding force between the grey cloth fiber and the printing color paste, thereby improving the anti-stripping ability of the fabric.

[0058] 5. Combined with the above table, the comparison of the test data of H, I printed fabrics and A printed fabrics shows that the addition of oak bark powder and the treatment of ordinary oak bark extracts with plant mucus can further improve the anti-stripping ability of printed fabrics, but the improvement of softness is not obvious. Oak bark extracts have strong chelating ability and antioxidant properties, which help to form a stronger bond with the surface of grey cloth fibers during the printing process, thereby enhancing the firmness of the printing. Plant mucus has good film-forming and adhesion properties, and can penetrate into the interior of the grey cloth fibers to prevent the printing from stripping.

[0059] The above-mentioned embodiment only expresses one implementation mode of the present invention, and its description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A peel-resistant printed fabric, the raw materials for preparing which include grey cloth, an impregnation liquid for pre-treating the grey cloth, and a printing paste for printing the grey cloth, characterized in that: The raw materials for preparing the impregnation solution include, by weight, 5-7 parts of rare earth-chitosan complex, 0.5-1 part of baking soda and 50-60 parts of ethanol; The rare earth-chitosan complex is obtained by treating rare earth and chitosan with tartaric acid; The raw materials for preparing the printing paste include, by weight, 10-15 parts of oak bark powder, 2-4 parts of seaweed extract, 2-4 parts of coral extract, 1-3 parts of xanthan gum, 1-3 parts of angustifolia gum, 5-7 parts of colorant and 100-120 parts of deionized water; The oak bark powder is obtained by treating oak bark extract with plant mucus.

2. The anti-stripping printed fabric according to claim 1, characterized in that: The mass ratio of the rare earth, chitosan and tartaric acid is 1:3-3.5:0.7-0.

8.

3. The anti-stripping printed fabric according to claim 2, characterized in that: The rare earth is a mixture of lanthanum oxide powder and cerium oxide powder with a particle size range of 10-50 nm, and the mass ratio of the lanthanum oxide powder to the cerium oxide powder is 1:1-1.

2.

4. The anti-stripping printed fabric according to claim 3, characterized in that: The preparation steps of the rare earth-chitosan complex are as follows: dispersing chitosan in 5-7 times the mass of deionized water to obtain a chitosan solution, dispersing rare earth in 5-7 times the mass of deionized water to form a rare earth solution, slowly adding the rare earth solution to the chitosan solution under stirring, slowly adding tartaric acid after mixing evenly, applying ultrasound with a frequency of 15-20KHz and a time of 25-35min to the dispersion after mixing evenly, then controlling the temperature of the dispersion to 50-55°C, the pH to 5-6, the reaction time to 2-3h, and after the reaction is completed, cooling the mixture, standing it to allow the complex to precipitate, and drying the precipitate to obtain the rare earth-chitosan complex.

5. The anti-stripping printed fabric according to claim 1, characterized in that: The preparation steps of the impregnation solution are: dispersing the rare earth-chitosan complex in ethanol, mixing evenly to obtain a rare earth-chitosan complex solution, dispersing baking soda in the remaining ethanol, mixing evenly to obtain a baking soda solution, and then slowly mixing the rare earth-chitosan complex solution and the baking soda solution, and gently stirring until they are uniform.

6. The anti-stripping printed fabric according to claim 1, characterized in that: The mass ratio of the oak bark extract to the plant mucus is 1:0.3-0.5; The plant mucus is one or a mixture of aloe mucus, cactus mucus and okra mucus.

7. The anti-stripping printed fabric according to claim 6, characterized in that: The preparation steps of the oak bark powder are as follows: dispersing the oak bark extract in 8-10 times the mass of deionized water, adding plant mucus after mixing evenly, applying ultrasound with a frequency of 20-25KHz and a time of 10-15min to the dispersion after mixing evenly, then controlling the temperature of the dispersion to 40-50°C, the pH to 4-5, standing for 1-2h, and after the reaction is completed, drying in a low-temperature dryer until a solid is formed, and obtaining the oak bark powder after crushing.

8. The anti-stripping printed fabric according to claim 1, characterized in that: The preparation steps of the printing paste are as follows: dissolving xanthan gum and angustifolia gum in deionized water and standing for 15-20 minutes to obtain a colloid mixture, dispersing oak bark powder, seaweed extract and coral extract in deionized water in another container in turn, adding the colloid mixture thereto after mixing evenly, adding colorant and deionized water based on the required color depth and viscosity after mixing evenly, applying ultrasound with a frequency of 20-25KHz and a time of 15-20 minutes after mixing evenly to obtain the printing paste.

9. The anti-stripping printed fabric according to claim 1, characterized in that: The grey cloth is woven from polyester fibers.

10. A method for processing the anti-stripping printed fabric according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Spray the impregnation liquid onto the surface of the grey cloth according to the printing template and leave it in a ventilated environment for 20-30 minutes; S2, controlling the temperature of the printing paste to 50-55°C, and printing the pattern according to the printing template; S3. After printing is completed, the grey cloth is dried and cured to obtain a peel-resistant printed fabric.